Venereal Transmission of Cancer: A Study - Shah, Shruti (Homœopathic Links, 2016)
Miasms have a tendency to remain dormant for years and they are the fundamental cause of chronic diseases. Two of the three known miasms—Sycosis and Syphilis—are venereal. This means they can infect the DNA as well as can get transmitted sexually. Cancer is a complex miasmatic disease. To understand the possibility of its venereal transmission and also when a partner's family have a positive family history of cancer, a study was done on 54 known cases of cancer. The cancer patients were surveyed under three categories: (1) a history of past or present addiction, (2) a history of cancer in one's own family, (3) a history of cancer in the spouse or in his or her family. Analysis showed that, along with addiction and heredity, occurrence of cancer is also found to be associated significantly when there is a positive history of cancer in spouse or in his or her family. This is a soft statistical proving to Dr. Hahnemann's concept of venereal nature of chronic diseases.
Keywords: Miasms; Cancer; Venereal transmission